Leber’s Congenital Amaurosis and its Complications – A Very Rare Presentation - Sujit Das; Sakshi Singh; Aastha Agarwal; Ram Monohar Misra (Delhi Journal of Ophthalmology)
Leber’s congenital amaurosis is one of the most severe forms of retinal dystrophies responsible for congenital blindness. It accounts for 10%–18% of congenital blindness cases. It is characterized by at least three findings: severe and early visual impairment, sluggish or near-absent pupillary responses, and severely subnormal or nondetectable electroretinogram. Some patients exhibit solely retinal blindness and show evidence of multisystemic involvement. Here, in this article, we are presenting a case of complicated Leber’s congenital amaurosis with cataract and primary hyperplastic primary vitreous along with neurodevelopmental delay.